Economic burden of smoking in China, 2000. (24th May 2006) - Sung, H-Y; Wang, L; Jin, S; Hu, T-W; Jiang, Y
Abstract : Objective: To assess the health-related economic burden attributable to smoking in China for persons aged 35 and older. Methods: A prevalence-based, disease-specific approach was used to estimate the smoking attributable direct costs, indirect morbidity costs, and costs of premature deaths caused by smoking-related diseases. The primary data source was the 1998 China National Health Services Survey, which contains the smoking status, medical utilisation, and expenditures for 216 101 individuals. Results: The economic costs of smoking in 2000 amounted to $5.0 billion (measured in 2000, US$) in total and $25.43 per smoker (⩾ age 35). The share of the economic costs was greater for men than women, and greater in rural areas than in urban areas. Of the $5.0 billion total costs, direct costs were $1.7 billion (34% of the total), indirect morbidity costs were $0.4 billion (8%), and indirect mortality costs were $2.9 billion (58%). The direct costs of smoking accounted for 3.1% of China's national health expenditures in 2000. Conclusion: The adverse health effects of smoking constitute a huge economic burden to the Chinese society. To reduce this burden in the future, effective tobacco control programmes and sustained efforts are needed to curb the tobacco epidemic and economic losses.